2016
DOI: 10.1002/bdm.1979
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do We Know Our Inner Daredevil? Probing the Relationship Between Self‐Report and Behavioral Measures of Risk Taking

Abstract: To measure a person's risk‐taking tendency, research has relied interchangeably on self‐report scales (e.g., “Indicate your likelihood of engaging in the risky behavior”) and more direct measures, such as behavioral tasks (e.g., “Do you accept or reject the risky option?”). It is currently unclear, however, how the two approaches map upon each other. We examined the relationship between self‐report likelihood ratings for risky choice in a monetary gamble task and actual choice, and tested how the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Our findings seem to reflect a general tendency toward caution in financial contexts with advancing age, at least in comparison with the views of others. This is in line with the finding that older adults are less willing than younger adults to take risks on a range of monetary gambling tasks [4,23,[28][29][30][31], although such tasks typically involve gambling on small and inconsequential monetary gains and losses (for a discussion of this issue see [32]).…”
Section: Perceptions Of Risk For Older Adults 19supporting
confidence: 78%
“…Our findings seem to reflect a general tendency toward caution in financial contexts with advancing age, at least in comparison with the views of others. This is in line with the finding that older adults are less willing than younger adults to take risks on a range of monetary gambling tasks [4,23,[28][29][30][31], although such tasks typically involve gambling on small and inconsequential monetary gains and losses (for a discussion of this issue see [32]).…”
Section: Perceptions Of Risk For Older Adults 19supporting
confidence: 78%
“…(4,5) Many older adults must also decide whether to surrender their driving privileges and compromise their mobility on the basis of doctors' recommendations and the advice of friends and family. (6) Psychological literature has often reported that older adults exercise caution in situations that involve risk, (7)(8)(9) particularly in health, recreational, and financial contexts. (10) Yet, are older adults also more responsive to warnings about potential risk?…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, we studied risky decision making in younger and healthy older adults in the local community. In contrast with previous approaches that have used monetary gambles (9,17) or examples of extreme activities (e.g., bungee jumping), (38) we designed four everyday scenarios about which people of all ages would have some relevant knowledge or experience. Scenarios described visiting a family member in a local hospital despite poor weather (weather scenario), using an ATM machine in the street (fraud scenario), ordering a high-salt meal at a restaurant (health scenario), and accepting a car ride without access to a seat belt (safety scenario).…”
Section: Introductionmentioning
confidence: 99%
“…Lönnqvist, Verkasalo, Walkowitz, & Wichardt, 2014;Rolison & Pachur, 2016). Behavioural measures are performance-based, and therefore objective, and enable execution of well-controlled manipulations of parameters of each decision (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When those factors are accounted for, older adults risk just as much -and sometimes even more -than young people (see e.g. Huang, Wood, Berger, & Hanoch, 2013;Mamerow et al, 2016;Rolison & Pachur, 2016). In light of all the above, it is plausible that youths' overall higher propensity to take all kinds of risks is also only a "reasonable speculation" (Willoughby et al, 2013), validating a targeted research approach.…”
Section: Introductionmentioning
confidence: 99%